Pengaruh Penambahan Bio-filler Serbuk Pelepah Pisang pada Sifat Termal, Reologi, dan Mekanik Komposit Termoplastik Berbasis Polipropilena - Nisa, Khadijah Sayyidatun; Aryanti, Fitria Ika; Wedian, Ariya (Talenta Publisher (Universitas Sumatera Utara), 2025)
This study examines the effect of banana stem powder (SPP) addition on the thermal, rheological, and mechanical properties of polypropylene (PP) composites with the addition of stearic acid. The composites were made with variations of PP:SPP of 100:0%, 98:2%, 96:4%, and 94:6% by weight. Differential Scanning Calorimetry testing showed the highest melting temperature of 165.4°C at 4% SPP, while the highest crystallinity of 42.64% was obtained at 2% SPP. The highest flow rate was obtained at 2% SPP of 8.83 g/10 min, and there was a decrease in the flow rate at 4% and 6% SPP. The tensile strength test results showed a decrease, from 30.10 MPa in pure PP to 23.40 MPa at 2% SPP. The results indicate that SPP can improve the thermal and rheological properties of the composite within certain limits, but excessive addition decreases the mechanical strength.